বাংলা সাহিত্যে শিশু (১৯০১-২০০০) - বদিউজজামান. (ঢাকা : বাংলাদেশ এশিয়াটিক সোসাইটি, 2002)
Study on children as reflected in Bengali literature from 1901 to 2000; covers publications both from Bengal, India and Bangladesh.
Includes bibliographical references (p. [359]-368) and index.
In Bengali.
Keywords: Bengali literature -- 20th century -- History and criticism; Children in literature